The effect of fumaric acid-sodium bicarbonate on the green tea effervescent granuleâs quality made by dry granulation - Lestari, Agatha Busi susiati; Trisusilawati, Maria Yuli (INDONESIAN JOURNAL OF PHARMACY, 2010)
Tea plant (CamelliaÂ  sinensisÂ  L.)Â  had beenÂ  knownÂ  toÂ  contains epigallocathecin gallate (EGCG) that can be used to maintain the healthy. In this research, the green tea wasÂ  tried to be formulated in effervescent dosage form, withÂ  theÂ  focusÂ  onÂ  theÂ  effectÂ  amongÂ  fumaricÂ  acid,Â  sodiumÂ  bicarbonate,Â  andÂ  the interactionÂ  betweenÂ  fumaricÂ  acidÂ  andÂ  sodiumÂ  bicarbonateÂ  onÂ  theÂ  greenÂ  tea extractÂ  effervescent granuleâsÂ  physical properties, that made by dry granulation method.Â  PhysicalÂ  propertiesÂ  ofÂ  effervescentÂ  granuleÂ  thatÂ  beenÂ  studyÂ  were moistureÂ  content,Â  flowÂ  rate,Â  disintegrationÂ  time,Â  andÂ  pHÂ  ofÂ  theÂ  solution.Â  The result showed that sodium bicarbonate was dominant in determining pH, granule flowÂ  rateÂ  andÂ  moistureÂ  contentÂ  ofÂ  granule,Â  whereasÂ  fumaricÂ  acidÂ  dominantÂ  in disintegration time of effervescent granule.Key words: green tea, fumaric acid, effervescent granule, dry granulation